DETERMINATION OF METRONIDAZOLE MICROPARTICLE CONTENTS IN THE HEMISELLULOSE MATRIX OF CORN COB USING ULTRAVIOLET SPECTROPHOTOMETRY - Dalimunthe, Gabena Indrayani; Rani, Zulmai; Rambe, Robiatun (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Microparticles can be an accurate drug delivery agent, reducing drug concentration in the target and providing an effective delivery system for substances that are slightly soluble in water. Corn cobs contain the most hemicellulose, and this hemicellulose can be employed as a matrix to restrict medication release if administered orally. The purpose of this study is to use UV spectrophotometry to evaluate the concentration of metronidazole microparticles in the hemicellulose matrix of corn cobs. This research is divided into two stages: separating hemicellulose from corn cobs and characterization of hemicellulose, which includes visual organoleptics, taste, smell, and form. Solubility test in alkaline conditions (NaOH), followed by FTIR test using the KBr pellet method with typical peaks seen in the FTIR spectrum, SEM test to get structural morphology, and PSA test to determine particle size and distribution of representative samples. After the microparticles are formed, further characterization is carried out, including an organoleptic test, solubility test, PSA test, FTIR test, and SEM test. Next, the levels of metronidazole microparticles in the corncob hemicellulose matrix were determined using ultraviolet spectrophotometry by comparing metronidazole tablets on the market. The concentration of metronidazole microparticle sample in the corncob hemicellulose matrix was determined to be 80.12 0.5290%, and the concentration of metronidazole tablets on the market was 100.51 0.7576%, which meets the requirements for metronidazole tablet concentration, namely not less than 90.0% and not more than 110% of the amount stated on the label.